2004
DOI: 10.1088/0953-8984/16/18/008
|View full text |Cite
|
Sign up to set email alerts
|

Indirect nuclear exchange coupling and electronic structure of the layered semiconductor TlS: NMR study and band structure calculation

Abstract: We have studied the electronic structure of the layered semiconductor TlS by means of 203 Tl and 205 Tl NMR and band structure calculation. The crystal structure of this compound is built from the metal-chalcogen layers formed of linked Tl 3+ S 2− 4 tetrahedra and Tl + ions located between the layers. Our experiments show significant interlayer indirect exchange coupling of thallium nuclei. Since the distances between thallium ions essentially exceed the sum of their ionic radii, it is concluded that such co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…However NMR studies on similar samples of Tl-As-Se [20] have indicated the possibility that thallium can enter the network with either a valency of one or three. NMR on the crystalline chalcogenides containing thallium [21,22] also indicates two valencies for the thallium. The chemical shift values tend to indicate that the valency of one leads to a bonding similar to that in thallous chloride which is ionic in nature.…”
Section: Thallium Bonding Chemically Ordered Network and The Variatimentioning
confidence: 94%
“…However NMR studies on similar samples of Tl-As-Se [20] have indicated the possibility that thallium can enter the network with either a valency of one or three. NMR on the crystalline chalcogenides containing thallium [21,22] also indicates two valencies for the thallium. The chemical shift values tend to indicate that the valency of one leads to a bonding similar to that in thallous chloride which is ionic in nature.…”
Section: Thallium Bonding Chemically Ordered Network and The Variatimentioning
confidence: 94%
“…This idea of two valencies for thallium is suggested on the basis of 205 Tl NMR studies on amorphous As-Se-Tl samples [24]. Thallium NMR of crystalline ternary chalcogenides containing thallium also indicate the presence of these two types of valencies for thallium [25,26].…”
Section: The Composition Dependence Of Thermal Diffusivitymentioning
confidence: 99%
“…We measured NMR spectra and spin-lattice relaxation rates of 203 Tl and 205 Tl isotopes, that have spin I =1/2 and are excellent probes in studying the electronic structure of compounds. [1][2][3][4][5][6][7][8][9][10][11][12][13] Our measurements show clear distinction in the indirect nuclear exchange coupling and Knight shift in the bulk and nanorod Tl 2 Se samples, reflecting noticeable difference in their electronic structure. Though Mooser and Pearson 14 mentioned that bulk Tl 2 Se behaves as a metal, we observed that it exhibits Korringa-like spin-lattice relaxation behavior only at low temperatures.…”
mentioning
confidence: 99%
“…6 MHz, corresponding to the Larmor frequency of 205 Tl isotope in the magnetic field B 0 = 1.17 T. The large S 2 values observed imply that the line shape is related to essential indirect nuclear exchange interactions among the Tl nuclei that are characteristic for most of Tlcontaining compounds. [1][2][3][4][5][6][7][8][9][10][11][12][13] Van Vleck has shown 19 that in the exchange-coupled nuclear systems, described by the Hamiltonian Ĥ = J jk I j I k , only exchange interaction between unlike spins contributes to the second moment of the NMR spectrum. Therefore in a crystal that contains two different isotopes, the ratio of their second moments is inversely proportional to the ratio of the isotope contents.…”
mentioning
confidence: 99%
See 1 more Smart Citation